Comparing clinico-demographics and neuropsychiatric symptoms for immigrant and non-immigrant aged care residents living with dementia: a retrospective cross-sectional study from an Australian dementia-specific support service - Chejor, Pelden; Atee, Mustafa; Cain, Patricia; Whiting, Daniel; Morris, Thomas; Porock, Davina (BioMed Central, 2023)
Background Neuropsychiatric symptoms of dementia such as agitation and aggression are common in people living with dementia. The presentation of neuropsychiatric symptoms is influenced by the cultural background of people living with dementia. Further, identifying factors contributing to neuropsychiatric symptoms may be complicated if people living with dementia are immigrants or from non-English-speaking backgrounds. Most of what is known about differences in neuropsychiatric symptoms between racial and ethnic groups living with dementia come from community-based samples. This study investigated differences in clinico-demographics and neuropsychiatric symptoms between immigrants and non-immigrants living with dementia in residential aged care homes who were referred to two Dementia Support Australia programs.